Mercury uptake and phytotoxicity in terrestrial plants grown naturally in the Gumuskoy (Kutahya) mining area, Turkey - Şaşmaz, Merve; Akgül, Bünyamin; Yıldırım, Derya; Şaşmaz, Ahmet (My University, 2016)
This study investigated mercury (Hg) uptake and transport from the soil to different plant parts by documenting the distribution and accumulation of Hg in the roots and shoots of 12 terrestrial plant species, all of which grow naturally in surface soils of the Gumuskoy Pb-Ag mining area. Plant samples and their associated soils were collected and analyzed for Hg content by ICP-MS. Mean Hg values in the soils, roots, and shoots of all plants were 6.914, 460, and 206 mg kg¡1, respectively and lower than 1. The mean enrichment factors for the roots (ECR) and shoots (ECS) of these plants were 0.06 and 0.09, respectively and lower than 1. These results show that the roots of the studied plants prevented Hg from reaching the aerial parts of the plants. The mean translocation factor (TLF) was 1.29 and higher than 1. The mean TLF values indicated that all 12 plant species had the ability to transfer Hg from the roots to the shoots but that transfer was more efficient in plants with higher ECR and ECS. Therefore, these plants could be useful for the biomonitoring of environmental pollution and for rehabilitating areas contaminated by Hg.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Wild plants; Phytoremediation; Mining area; Mercury uptake